Parateksty jako wyraz koncepcji przekładu - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2017)
Paratexts as an Expression of the Concept of Translation There is a connection between paratexts and the translators’ strategy, between the attitude towards strangeness and the concept of translation from the perspective of the hosting culture, represented by translators, critics and researchers. They always define the literary and cultural awareness of individuals and of the epoch. In relation to the main text, they create a new literary and mental reality basing on specific translational solutions at the level of language and culture. In the translators’ afterword to Slovenian translations of Polish literature in the years 1987—2014, the concept of translation was formulated both directly and indirectly, which places the original in the center of both the process of translation and of research in translation. They are the result of the interaction between the translator and the original, and between the translator and the reader of the translation. The concluded (and continued) transaction between the translator and the reader includes a promise of taking the latter into a fascinating, unknown world and assuring him of his role as an expert. The afterword has a cognitive and mediating function. Keywords: translation, paratext, afterword, Polish literature, Slovenian translators